Cytotoxicity and Effects of a New Calcium Hydroxide Nanoparticle Material on Production of Reactive Oxygen Species by LPS-Stimulated Dental Pulp Cells - de Souza, Gabriela Leite; Almeida Silva, Anielle Christine; Dantas, Noélio Oliveira; Silveira Turrioni, Ana Paula; Moura , Camilla Christian Gomes (Iranian Endodontic Journal, 2020)
Introduction: The aim of this study was to synthesize and characterize calcium hydroxide (CH) nanoparticles [CH-NP] and compare the cytotoxicity of these materials with that of mineral trioxide aggregate (White MTA) in human dental pulp mesenchymal cells (hDPMCs) stimulated by lipopolysaccharide (LPS). Methods and Materials: The CH-NP were synthesized by the co-precipitation method, and the physical properties were investigated through X-ray diffraction, scanning electron microscopy (SEM) and energy dispersive x-ray spectrometry (EDS). LPS-stimulated hDPMCs were placed in contact with different dilutions of culture media previously exposed to CH-NP and white MTA for 24 h. The groups were tested for cell viability by MTT formazan and Alamar Blue assays, the production of nitric oxide (NO) by Griess method and the production of reactive oxygen species (ROS) by means of the fluorescent oxidant-sensing probe 2’,7’-dichlorodihydrofluorescein diacetate (DCFH-DA). Control groups for viability test were maintained in DMEM (not LPS-stimulated). For NO and ROS production, negative control group was cells in DMEM, and positive control was cells stimulated by LPS. The results were statistically analyzed by two-way ANOVA, Tukey’s test and Dunnett’s test (ɑ=0.05). Results: The results showed that the cell viability remained above 50% in all materials, independent of the dilution in MTT formazan and Alamar Blue tests. MTA showed a reduction in NO production at dilutions of 1:4 to 1:32 compared with the positive control group (P<0.05). The tested materials exhibited lower ROS production by DPMCs than that by cells in the positive control group (P<0.05), and similar ROS production to the negative control group (P>0.05). Conclusion: The outcomes of present in vitro study showed that MTA and [CH-NP] were not cytotoxic materials, with MTA closer to the results of control group (DMEM). MTA and [CH-NP] reduced ROS production at basal levels, with MTA inhibiting NO production at higher dilutions.